Correction: Programmable RNA microstructures for coordinated delivery of siRNAs. Issue 15 (31st March 2017) - Stewart, Jaimie Marie; Viard, Mathias; Subramanian, Hari K. K.; Roark, Brandon K.; Afonin, Kirill A.; Franco, Elisa
Abstract : Correction for 'Programmable RNA microstructures for coordinated delivery of siRNAs' by Jaimie Marie Stewart et al., Nanoscale, 2016, 8, 17542–17550.